Harnessing innate lung anti-cancer effector functions with a novel bacterial-derived immunotherapy. (4th March 2018) - Bazett, Mark; Costa, Amanda M.; Bosiljcic, Momir; Anderson, Rebecca M.; Alexander, Matthew P.; Wong, Stephanie W. Y.; Dhanji, Salim; Chen, Jenny MH; Pankovich, Jim; Lam, Stephen; Sutcliffe, Simon; Gunn, Hal; et al.
ABSTRACT: Acute infection is known to induce strong anti-tumor immune responses, but clinical translation has been hindered by the lack of an effective strategy to safely and consistently provoke a therapeutic response. These limitations are overcome with a novel treatment approach involving repeated subcutaneous delivery of a Klebsiella -derived investigational immunotherapeutic, QBKPN. In preclinical models of lung cancer, QBKPN administration consistently showed anti-cancer efficacy, which was dependent on Klebsiella pre-exposure, but was independent of adaptive immunity. Rather, QBKPN induced anti-tumor innate immunity that required NK cells and NKG2D engagement. QBKPN increased NK cells and macrophages in the lungs, altered macrophage polarization, and augmented the production of cytotoxic molecules. An exploratory trial in patients with non-small cell lung cancer demonstrated QBKPN was well tolerated, safe, and induced peripheral immune changes suggestive of macrophage polarization and reduction of PD-1 and PD-L1 expression on leukocytes. These data demonstrate preclinical efficacy, and clinical safety and tolerability, for this cancer immunotherapy strategy that exploits innate anti-tumor immune mechanisms.